2018
DOI: 10.1016/j.scitotenv.2018.02.216
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of toxic action of copper and copper nanoparticles in two Amazon fish species: Dwarf cichlid (Apistogramma agassizii) and cardinal tetra (Paracheirodon axelrodi)

Abstract: Copper oxide nanoparticles (nCuO) are widely used in boat antifouling paints and are released into the environment, potentially inducing toxicity to aquatic organisms. The present study aimed to understand the effects of nCuO and dissolved copper (Cu) on two ornamental Amazon fish species: dwarf cichlid (Apistogramma agassizii) and cardinal tetra (Paracheirodon axelrodi). Fish were exposed to 50% of the LC for nCuO (dwarf cichlid 58.31μgL and cardinal tetra 69.6μgL) and Cu (dwarf cichlid 20μgL and cardinal tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 59 publications
6
39
0
Order By: Relevance
“…The addition of cytochrome c led to only a small percentage increase in respiration rate (Table 1), confirming that the preparations were of high quality. In comparison to semi-isolated, Dounce-homogenized, gill tissues (Braz-Mota et al, 2018), our preparation shows greater RCR values (7.4 versus 2.6-5.5), further confirming the high quality of mitochondrial preparations using this technique (Table 1). It is interesting to note that our respiration values are lower than those reported by Braz-Mota et al 2018, although this is expected and has been shown in studies comparing different mitochondrial preparations in other taxa (Saks et al, 1998;Picard et al, 2011;Mahalingam et al, 2017).…”
Section: Resultssupporting
confidence: 64%
“…The addition of cytochrome c led to only a small percentage increase in respiration rate (Table 1), confirming that the preparations were of high quality. In comparison to semi-isolated, Dounce-homogenized, gill tissues (Braz-Mota et al, 2018), our preparation shows greater RCR values (7.4 versus 2.6-5.5), further confirming the high quality of mitochondrial preparations using this technique (Table 1). It is interesting to note that our respiration values are lower than those reported by Braz-Mota et al 2018, although this is expected and has been shown in studies comparing different mitochondrial preparations in other taxa (Saks et al, 1998;Picard et al, 2011;Mahalingam et al, 2017).…”
Section: Resultssupporting
confidence: 64%
“…CuNPs were less toxic than dissolved copper for the two studied fish species, namely dwarf cichlid (Apistogramma agassizii) and cardinal tetra (Paracheirodon axelrodi). Fishes were exposed to 50% of the LC50 for CuO-NPs (dwarf cichlid, 58.31 μg/L; cardinal tetra, 69.6 μg/L) and Cu (dwarf cichlid, 20 μg/L; cardinal tetra, 22.9 μg/L) for 24, 48, 72, and 96 h. Oxidative stress was promoted in the dwarf cichlid [ 166 ]. CuNPs were also shown to be toxic to tilapia, a freshwater edible fish, in comparison to dibutyltin at an exposure concentration of 15 mg/L, inducing oxidative stress and hindering fish growth and development [ 167 ].…”
Section: Overview Of Organ Toxicity In Fish Induced By Copper and mentioning
confidence: 99%
“…There is currently a significant gap in our knowledge about CuO-NPs toxicity to aquatic animals. In general, the Cu(O) NPs toxicity may be a potential environmental concern for crustaceans, as LC50 values are within an order of magnitude of predicted wastewater concentrations, while chronic and developmental toxicity are a more relevant concern for fishes (Braz-Mota et al 2018). A few studies have noted bioactivity in these animals at high concentrations (20 μg L -1 ).…”
Section: Toxicity On Aquatic Animalsmentioning
confidence: 99%
“…Copper (Cu) is a naturally occurring ubiquitous element present in the environment with a concentration around 60 g per ton in the Earth's crust (Ojha et al 2017) and essential micronutrient for plant growth at certain concentrations and is known to play important roles in mitochondrial respiration, hormone signalling, cell wall metabolism, iron mobilization, and electron transport (Yruela 2009). However, at higher concentrations, Cu is generally toxic to plants and other organisms including algae, mussels, crustaceans, and fish (Aruoja et al 2009;Braz-Mota et al 2018;Katsumiti et al 2018;Ruiz et al 2015). While there is no data available on the concentration of CuO-NPs in the soil total Cu could range from 2-100 mg kg -1 in unpolluted soils (Nagajyoti et al 2010).…”
Section: Introductionmentioning
confidence: 99%